Improving ESL learners' academic text construction through a collaborative task - Yong, Mei Fung (Universiti Putra Malaysia Press, 2011)
Many ESL writing instructors incorporate some form of pair or group work at some stage of the writing process to provide their students the opportunity to brainstorm ideas, plan, and co-construct knowledge with their peers. Another reason is to encourage students to work independently from the teacher with the intention that they will be more autonomous. This paper reports on a qualitative study which examines how one group of tertiary ESL learners in an academic writing course jointly produce an academic essay during one collaborative task. This study highlights some critical incidents pertaining to the students' roles, their behaviours, and instances that contribute to knowledge and text construction during the group work. The findings showed that cumulative talk and use of questions moved the group discussion forward while negotiation helped the learners to test ideas at a deeper level. The learners also shared their expertise during text construction. The affective conflict which the group encountered during the collaboration also helped them to deal with differing viewpoints and maintaining coherence in the group.